2001
DOI: 10.1079/bjn2000216
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the doubly-labelled water technique in the domestic dog (Canis familiaris)

Abstract: We validated doubly-labelled water (DLW) by comparison to indirect calorimetry and food intake±mass balance in eight Labrador dogs (24±32 kg) over 4 d. We used several alternative equations for calculating CO 2 production, based on the single-and two-pool models and used two alternative methods for evaluating the elimination constants: two-sample and multiplesampling. In all cases the DLW technique overestimated the direct estimate of CO 2 production. The greatest overestimates occurred with the single-pool mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Measures of isotope enrichment were based on independent analysis of two subsamples of the water distilled from the blood samples. Because our previous validation study in Labradors (Speakman et al, 2001b) had indicated the two-pool model was superior, we used this model to estimate CO 2 production. The error in individual estimates was determined using the iterative procedures outlined in Speakman (1995).…”
Section: Daily Energy Expenditurementioning
confidence: 99%
See 1 more Smart Citation
“…Measures of isotope enrichment were based on independent analysis of two subsamples of the water distilled from the blood samples. Because our previous validation study in Labradors (Speakman et al, 2001b) had indicated the two-pool model was superior, we used this model to estimate CO 2 production. The error in individual estimates was determined using the iterative procedures outlined in Speakman (1995).…”
Section: Daily Energy Expenditurementioning
confidence: 99%
“…The animals were injected via a forelimb vein with an isotonic mix of labelled water containing both 18 O and 2 H, following collection of a blood sample to establish background isotope enrichments. A blood sample was collected from the contralateral forearm at 6 h post-injection, established previously (Speakman et al, 2001b) as the time required for the injected isotopes to reach complete isotopic equilibrium in the body water of dogs of this size. We collected blood at 24-h intervals for a further 4 days.…”
Section: Daily Energy Expenditurementioning
confidence: 99%
“…As it comes down to the biological plausibility of the observed association, it is conceivable that iron deficiency may affect both innate and cellular immune responsiveness [26,27] at the level of the vaginal mucosa, though we did not identify any previous study on micronutrient status and bacterial vaginosis. The significant association of iron deficiency anaemia with infection has however extensively been demonstrated and most importantly, these effects have been attributed to the adverse effects of iron deficiency on the immune system, even in the setting of mild micronutrient deficiencies [26,27,29].…”
Section: Discussionmentioning
confidence: 99%
“…The significant association of iron deficiency anaemia with infection has however extensively been demonstrated and most importantly, these effects have been attributed to the adverse effects of iron deficiency on the immune system, even in the setting of mild micronutrient deficiencies [26,27,29]. Interestingly, our observations on the association between iron deficiency and bacterial vaginosis concur with the consistent association between maternal iron deficiency in early pregnancy and a greater risk of preterm delivery [28,29] on one hand, and with the strong and consistent association between bacterial vaginosis in early pregnancy and preterm delivery [11,12,20] on the other hand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation